The Effects of Morus alba and Acacia catechu on Quality of Life and Overall Function in Adults with Osteoarthritis of the Knee - Douglas S. Kalman; Susan J. Hewlings (Journal of Nutrition and Metabolism)
The purpose of this study was to determine the effects of UP1306 on discomfort and function in adults with osteoarthritis of the knee. In a randomized, double-blinded, placebo-controlled, parallel design, 135 subjects received UP1306, a standardized, proprietary extract of Morus alba and Acacia catechu, glucosamine chondroitin, or placebo for 12 weeks. Discomfort, stiffness, and activities of daily living measured by the WOMAC questionnaire and VAS (pain/discomfort) were improved within all groups. Range of motion and distance walked were improved. There were no changes in TNFα levels for any of the products. There was a significant difference in urinary C-telopeptides of type II collagen (CTX-II), a marker of cartilage degradation between UP1306, and placebo after 12 weeks (p=0.029). All efficacy measurements were improved from baseline to most time-points for UP1306, the comparator, and placebo without a significant association between the products. There was a significant difference between the changes of uCTX-II for UP1306 and placebo after 12 weeks. Early intervention with UP1306 aimed at reducing bone and cartilage degradation through reported inhibition of catabolic proinflammatory pathways may help to prevent joint cartilage damage. This study is registered with Clinical Trial ID ISRCTN15418623.